IMPLEMENTASI NEUROPSIKOLOGIS DALAM MENCIPTAKAN LINGKUNGAN BELAJAR YANG KOMPATIBEL DI SEKOLAH DASAR - Manurung, Alberth; Yufiarti; Supena, Asep (Jurnal Ilmiah Pendidikan Citra Bakti, 2023)
The purpose of this study was to determine the extent to which teachers' understanding of a compatible learning environment and their efforts in implementing it. This study uses a descriptive qualitative method. The subjects of this study were 24 people consisting of 1 school principal, 18 class teachers, 3 religion teachers and 2 sports teachers at SDN Kenari 07 Pagi. Data collection was carried out through in-depth interviews. The results of the study show that the classroom teacher seems to have difficulty in creating a compatible environment. In addition, the researcher found several things that showed that the class teacher was not ready to create a compatible environment. For example, the condition of the school environment towards school facilities and infrastructure, the lack of preparation in creating a compatible environment, to the point where it is not appropriate to create a conducive atmosphere for children. Children's intelligence is certainly one of the priorities that they want to develop optimally. In addition, there are several other brain functions that are very important for their future success, such as creativity and emotional intelligence, there is one thing we need to pay attention to, namely the role of play in brain development. In our youth, our brains are very plastic, conditions where the brain is very easy to change, develop and be influenced by the environment.